2017
DOI: 10.1016/j.jallcom.2017.03.352
|View full text |Cite
|
Sign up to set email alerts
|

Defect structure and hardness in nanocrystalline CoCrFeMnNi High-Entropy Alloy processed by High-Pressure Torsion

Abstract: An equiatomic CoCrFeMnNi High-Entropy Alloy (HEA) produced by arc melting was processed by High-Pressure Torsion (HPT). The evolution of the microstructure during HPT was investigated after ¼, ½, 1 and 2 turns using electron backscatter diffraction and transmission electron microscopy. The spatial distribution of constituents was studied by energy-dispersive X-ray spectroscopy. The dislocation density and the twin-fault probability in the HPT-processed samples were determined by X-ray line profiles analysis. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(64 citation statements)
references
References 46 publications
5
59
0
Order By: Relevance
“…Formation of UFG microstructure after HPT at room temperature is well documented for various metallic materials [17] including high-entropy alloys [8][9][10][24][25][26]. The microstructure evolution during HPT is usually associated with the formation of low-angle grain boundaries at low strains and transformation of some of these low-angle subgrain boundaries into high-angle grain boundaries at higher strains giving rise to a considerable microstructure refinement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Formation of UFG microstructure after HPT at room temperature is well documented for various metallic materials [17] including high-entropy alloys [8][9][10][24][25][26]. The microstructure evolution during HPT is usually associated with the formation of low-angle grain boundaries at low strains and transformation of some of these low-angle subgrain boundaries into high-angle grain boundaries at higher strains giving rise to a considerable microstructure refinement.…”
Section: Discussionmentioning
confidence: 99%
“…A reduction of a grain size from 150 to 5 µm in the CoCrFeMnNi alloy increased the yield strength by a factor of two while maintained good ductility [6]. Severe plastic deformation of the CoCrFeNiMn alloy via high-pressure torsion (HPT) expectably refined the microstructure to a grain size d~40-50 nm and increased the microhardness of the alloy by a factor of~3 [8][9][10]. The ultimate tensile strength of the alloy after HPT was found to be~2000 MPa [8].…”
Section: Introductionmentioning
confidence: 99%
“…An abundance of investigations have emerged in the literature focusing on microstructural characteristics, defect evolution as well as mechanical properties for HEAs after SPD. [99][100][101][102][103][104][105][106][107][108][109] A recent work by Bhattacharjee et al 106 reported that the nanolamellar AlCoCrFeNi 2.1 HEA, which was achieved by cryorolling and annealing processes, exhibited a remarkable increase in both the yield strength and the ultimate tensile strength (UTS) without sacrificing too much ductility [ Fig. 8(a)].…”
Section: Grain Coarseningmentioning
confidence: 99%
“…Such unique characteristics were mainly attributed to the formation of a hierarchical microstructure after SPD. Heczel et al 108 quantified the defect evolution features such as dislocation density and twin-fault probability for an equiatomic CoCr-FeMnNi HEA produced by HPT and successfully explained the enhanced mechanical properties. In the powder scale, mechanical alloying (MA) (often corresponded with various sintering techniques) is another viable approach to fabricate nanostructured bulk metallic solids.…”
Section: Grain Coarseningmentioning
confidence: 99%
“…Aside from their interesting solidification behaviors, high-entropy alloys also present great potential to be used as structural materials due to their excellent properties such as high hardness [12,13], high strength [14][15][16], good oxidation resistance [17], soft-magnetic properties [18], softening resistance at high temperature [3], and recently revealed, perfect irradiation resistance [19]. Considering the existence of dozens of metallic elements, this new type of alloy implies that a large number of new multi-component metallic materials with excellent properties, which was neglected previously, might be fabricated to serve humanity.…”
Section: Introductionmentioning
confidence: 99%